Ethics and ICT: Why all the fuss?. Issue 2 (9th May 2016) - Warren, Matthew; Lucas, Richard
Abstract : Purpose: This paper aims to introduce a special section based on papers from Australasian Conference for Information Systems 2014. Design/methodology/approach: This paper comments on key contextualisation moments in relevant history. Findings: This paper describes the initiative in Australia to widen Information and Communication Technology ethics awareness. Originality/value: This is a new attempt to bring Ethics and Information Systems academics closer together.